Compatibility of X-ray computed tomography with plant gene expression, rhizosphere bacterial communities and enzyme activities. (28th May 2020) - Ganther, Minh; Yim, Bunlong; Ibrahim, Zeeshan; Bienert, Manuela Desiree; Lippold, Eva; Maccario, Lorrie; Sørensen, Søren Johannes; Bienert, Gerd Patrick; Vetterlein, Doris; Heintz-Buschart, Anna; Blagodatskaya, Evgenia; Smalla, Kornelia; et al.
Abstract: Non-invasive X-ray computed tomography (XRCT) is increasingly used in rhizosphere research to visualize development of soil–root interfaces in situ . However, exposing living systems to X-rays can potentially impact their processes and metabolites. In order to evaluate these effects, we assessed the responses of rhizosphere processes 1 and 24 h after a low X-ray exposure (0.81 Gy). Changes in root gene expression patterns occurred 1 h after exposure with down-regulation of cell wall-, lipid metabolism-, and cell stress-related genes, but no differences remained after 24 h. At either time point, XRCT did not affect either root antioxidative enzyme activities or the composition of the rhizosphere bacterial microbiome and microbial growth parameters. The potential activities of leucine aminopeptidase and phosphomonoesterase were lower at 1 h, but did not differ from the control 24 h after exposure. A time delay of 24 h after a low X-ray exposure (0.81 Gy) was sufficient to reverse any effects on the observed rhizosphere systems. Our data suggest that before implementing novel experimental designs involving XRCT, a study on its impact on the investigated processes should be conducted. Abstract : Visualization of the soil–plant system by X-ray computed tomography causes transient changes in root gene expression and microbial activity, but does not affect microbial community composition.